2019
DOI: 10.11604/pamj.2019.33.310.16894
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of pregnant women and health care workers on hepatitis B prevention in the Limbe and Muyuka health districts of the south west region of Cameroon

Abstract: IntroductionHepatitis B virus (HBV) infection is a major health problem worldwide owing to its high prevalence and significant morbidity and mortality. There are about 2 billion people living with HBV worldwide and over 360 million chronic carriers. The purpose of this study was to assess the knowledge and practices of pregnant women and health care workers in the ANC and maternity units on HBV infection and its transmission.MethodsAbout 270 women attending ANC and 31 health care workers were selected by conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24] However, sufficient knowledge of pregnant women has been reported in Cameroon. 25,26 Overall, we observed poor knowledge of HBV infection, transmission, and prevention in this study. Specifically, only 13.6% of pregnant women aware that hepatitis B is a virus in the current study.…”
mentioning
confidence: 68%
“…[15][16][17][18][19][20][21][22][23][24] However, sufficient knowledge of pregnant women has been reported in Cameroon. 25,26 Overall, we observed poor knowledge of HBV infection, transmission, and prevention in this study. Specifically, only 13.6% of pregnant women aware that hepatitis B is a virus in the current study.…”
mentioning
confidence: 68%
“…Considering the high prevalence of these infections, such infection‐related increase of risk of PD may affect a quite large population. For example, HCV was reported to affect 0.3% of population in Spain (Crespo et al, ), HP colonizes the gastric mucosa of more than half of the global human population (Suwarnalata et al, ), Malassezia was identified on more than 80% lesional skin (Arsic Arsenijevic et al, ), HBV affects 2 billion people worldwide and over 360 million chronic carriers (Yankam, Anye, Nkfusai, Shirinde, & Cumber, ). Therefore, clarification of the effect of such infection on risk of PD may assist the prevention and prediction of PD and bring benefits to a large population.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the great incidence of various diseases, this infection-related increase in PD risk could impact a sizable portion of the population. HCV was found to infect 0.3% of the population in Spain [ 61 ]; HP repopulates the stomach epithelium of almost fifty percent of the world’s population [ 62 ]; Malassezia was discovered on more than 80% of lesioned skin [ 63 ]; and HBV (hepatitis B virus) affects approximately 360 million chronic carriers and 2 billion individuals globally [ 64 ]. Knowing the effect of such infections on the chance of developing Parkinson’s disease is essential, thus helping with the detection and prediction of PD and benefitting a wide population.…”
Section: Infectious Risk Variablesmentioning
confidence: 99%